Aerobic-heterotrophic nitrogen removal through nitrate reduction and ammonium assimilation by marine bacterium Vibrio sp. Y1-5. (April 2017) - Li, Yating; Wang, Yanru; Fu, Lin; Gao, Yizhan; Zhao, Haixia; Zhou, Weizhi
Graphical abstract: ① and ② denoted utilizing sequence of the two nitrogen source. Highlights: Vibrio sp. Y1-5 exhibited efficient nitrate and ammonium removal in the single aerobic heterotrophic condition. Nitrogen removal was assimilatory nitrate reduction and ammonium assimilation. Neither N lost nor greenhouse gas Nx O producted in the process. The strain could tolerate 1600 mg/L ammonium with 844.6 mg/L ammonium removal. As a common pathogenic genus, Vibrio sp. Y1-5 was safe in aquatic ecosystems. Abstract: An aerobic marine bacterium Vibrio sp. Y1-5 was screened to achieve efficient nitrate and ammonium removal simultaneously and fix nitrogen in cells without N loss. Approximately 98.0% of nitrate (100 mg/L) was removed in 48 h through assimilatory nitrate reduction and nitrate reductase was detected in the cytoplasm. Instead of nitrification, the strain assimilated ammonium directly, and it could tolerate as high as 1600 mg/L ammonium concentration while removing 844.6 mg/L. In addition, ammonium assimilation occurred preferentially in the medium containing nitrate and ammonium with a total nitrogen (TN) removal efficiency of 80.4%. The results of nitrogen balance and Fourier infrared spectra illustrated that the removed nitrogen was all transformed to protein or stored as organic nitrogen substances in cells and no N was lost in the process. Toxicological studies with the brine shrimp species Artemia naupliia indicated that Vibrio sp. Y1-5 can be applied in aquatic ecosystems safely.